ANATOMI CINTA TOKOH DALAM NOVEL “SEGI TIGA” (KAJIAN PSIKOLOGI SASTRA) - Rodli Rodli; Yessy Soniatin; Aris Kurniadi; Ubaydillah Faqih (PENTAS : Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2021)
This study aims to describe (1) curiosity between characters in the novel "Triangles by Sapardi Djoko Damono" (2) the sense of attention between the characters in the novel "Segi Tiga Karya Sapardi Djoko Damono", as well as explain (3) the sense of affection between the characters in the novel "Segi Tiga Karya Sapardi Djoko Damono" This research is a qualitative descriptive research. The subject of this study is the novel "Segi Tiga Karya Sapardi Djoko Damono". This research is focused on problems related to the anatomy of love between figures of literary psychology studies. The data were analyzed with qualitative descriptive techniques, namely a research procedure with the results of presenting description data in the form of the author's speech in the novel "Segi Tiga Karya Sapardi Djoko Damono". The way data is collected is carried out by reading and recording techniques. The results of the study showed the anatomy of love between characters contained in the novel "Segi Tiga Karya Sapardi Djoko Damono". In accordance with the title of the novel "Triangle", there are three women, namely Gendis, Noriko, and Tia, the three women live a love story with one male character, namely Suryo. Suryo loves Noriko who he meets on a laptop screen, and then he encounters in a stall buying food. Meanwhile, Gendis and Tia are Suryo's own cousins, but because they are often together or too close, Suryo admits that they are not his cousins, Suryo will love like Noriko.